2017
DOI: 10.1111/joop.12184
|View full text |Cite
|
Sign up to set email alerts
|

How empathic concern helps leaders in providing negative feedback: A two‐study examination

Abstract: The role of leader empathic concern is examined in the context of negative feedback delivery. We argue that leader displays of empathic concern decrease negative affect and increase positive affect following negative feedback, resulting in more positive evaluations of the leader's feedback-giving effectiveness and improving the leader's promotability. In a video-based online experiment (Study 1) using a US sample (n = 177), both conditions experienced a decline in negative affect over the course of the feedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 53 publications
4
27
0
Order By: Relevance
“…Empirical evidence has supported the idea that leader-facilitated, down-regulation of negative emotion is linked to resilience-related outcomes (Little et al, 2016; Richard et al, 2016; Thiel et al, 2015; Young et al, 2017). For example, Little et al (2016) found that leaders who used situation modification and cognitive change to mitigate their followers’ negative emotions had followers who engaged in greater organizational citizenship behaviors (a form of discretionary performance) and enjoyed higher levels of job satisfaction.…”
Section: Interpersonal Emotion Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Empirical evidence has supported the idea that leader-facilitated, down-regulation of negative emotion is linked to resilience-related outcomes (Little et al, 2016; Richard et al, 2016; Thiel et al, 2015; Young et al, 2017). For example, Little et al (2016) found that leaders who used situation modification and cognitive change to mitigate their followers’ negative emotions had followers who engaged in greater organizational citizenship behaviors (a form of discretionary performance) and enjoyed higher levels of job satisfaction.…”
Section: Interpersonal Emotion Managementmentioning
confidence: 99%
“…Richard et al (2016) found that customer service employees whose leaders frequently demonstrated empathic concern (behavioral displays of warmth and compassion) exhibited less anger associated with customer mistreatment, and that lower level of anger reduced their likelihood of emotional deviance at work. Additionally, Young et al (2017) found that leader displays of empathy increased follower positive emotion following the receipt of negative feedback. Finally, qualitative data from Toegel et al’s (2012) research suggested that manager displays of empathy increase employee self-confidence, a key resilience promoting factor (Fisher et al, 2019; Luthans et al, 2006).…”
Section: Interpersonal Emotion Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Feedback researchers generally focus on stable negative and positive affect rather than momentary emotions. There is consistent evidence suggesting that negative feedback generates increased negative affect in employees, leading to unfavorable outcomes (e.g., Belschak & Den Hartog, 2009;Ilies & Judge, 2005;Young et al, 2017). However, the aggregation of discrete emotions into general affect can depress the specific utility of discrete emotions, given that discrete emotions have distinct motivational profiles (Lazarus & Cohen-Charash, 2001).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Similarly, a study by Thiel et al (2013) suggested that leader empathy may be important in attenuating negative emotions and defusing stress associated with a state of crisis. More recently, Young et al (2017) demonstrated that participants exposed to leader empathic concern while receiving negative feedback experienced a decline in negative affect and an increase in positive affect. They were also likely to evaluate the leader’s behavior as more effective than their control counterparts.…”
Section: Introductionmentioning
confidence: 99%